2017
DOI: 10.3389/fmicb.2017.01885
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum BSGP201683 Isolated from Giant Panda Feces Attenuated Inflammation and Improved Gut Microflora in Mice Challenged with Enterotoxigenic Escherichia coli

Abstract: In this work, we searched for an effective probiotic that can help control intestinal infection, particularly enterotoxigenic Escherichia coli K88 (ETEC) invasion, in giant panda (Ailuropoda melanoleuca). As a potential probiotic strain, Lactobacillus plantarum BSGP201683 (L. plantarum G83) was isolated from the feces of giant panda and proven beneficial in vitro. This study was aimed to evaluate the protective effect of L. plantarum G83 in mice challenged with ETEC. The mice were orally administered with 0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 62 publications
(51 reference statements)
4
24
0
Order By: Relevance
“…This result reveals that the small intestines have a strong ability to resist damage to gut integrity. This effect is consistent with that observed by Liu et al (2017) , who found higher mRNA expressions of claudin-1, occludin, and ZO-1 in mice fed with L. plantarum BSGP201683, especially after ETEC infection.…”
Section: Discussionsupporting
confidence: 92%
“…This result reveals that the small intestines have a strong ability to resist damage to gut integrity. This effect is consistent with that observed by Liu et al (2017) , who found higher mRNA expressions of claudin-1, occludin, and ZO-1 in mice fed with L. plantarum BSGP201683, especially after ETEC infection.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, chicks challenged with Clostridium showed signs of injury to intestine tissue, including the degeneration and necrosis of intestinal villi, with extensive round cell aggregations ( Figure 3B), wide hyperplasia of the villus epithelium, with a thickening and shortening of villi, together with metaplasia into goblet cells ( Figure 3C), as well as a degeneration of the villous epithelium with metaplasia of the columnar epithelium into goblet cells ( Figure 3D). These findings were in agreement with Wang et al [56], who found that supplementing the diet of broiler chicks with Lactobacillus plantarum protected the intestinal structure from enterotoxigenic Clostridium infection by reducing irritation and preserving the integrity of the intestinal epithelial layer [88]. It is thus widely accepted that probiotics can prevent gut diseases by improving the immunity of the gut [89], promoting the development of gut histomorphology [90] and modifying the gut microbiota [91].…”
Section: Liver and Intestinal Histopathological Signssupporting
confidence: 89%
“…In the state of intestinal microbiota dysbiosis, colonic epithelial oxidation increases and the anaerobic environment is affected; thus, facultative anaerobic Proteobacteria amplification is favored ( 37 ). A study of mice administered enterotoxigenic E. coli (ETEC) bacteria showed an increase in the abundance of Enterobacteriaceae ( 38 ). Our study also found a significant increase of Enterobacteriaceae abundance in the infected piglets.…”
Section: Discussionmentioning
confidence: 99%